2000
DOI: 10.1590/s0100-204x2000000200010
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do alumínio, nitrato e amônio sobre a composição de metabólitos nitrogenados e de carboidratos em Stylosanthes guianensis e S. macrocephala

Abstract: Quando o N foi suprido pela fonte nítrica, a adição do Al à solução nutritiva causou o aparecimento de sintomas de toxidez apenas em S. guianensis. Já em S. macrocephala, nessas condições, ocorreram aumentos nos teores de N-total, N-insolúvel, N-solúvel, N-nítrico e N-aminoácidos na parte aérea e nas raízes, seguidos de decréscimos nos teores de açúcares solúveis totais e redutores nas raízes.Termos para indexação: toxidez de Al, toxidez de amônio. EFFECTS OF ALUMINUM, NITRATE AND AMMONIUM ON THE METABOLIC NIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Some studies have shown that high concentrations of aluminum in the soil stimulate NR activity, as observed in the leguminous forage crop Stylosanthes macrocephala (Amaral et al, 2000) and in beans (Wang et al, 2010). Other authors have revealed that there is no change in NR activity in response to aluminum toxicity in the aerial parts of young plants of sugar cane cultivar IAC91-5155 (Carlin et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that high concentrations of aluminum in the soil stimulate NR activity, as observed in the leguminous forage crop Stylosanthes macrocephala (Amaral et al, 2000) and in beans (Wang et al, 2010). Other authors have revealed that there is no change in NR activity in response to aluminum toxicity in the aerial parts of young plants of sugar cane cultivar IAC91-5155 (Carlin et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Os níveis de Al utilizados neste trabalho (15 mg dm -3 ) foram considerados nocivos para as plantas, uma vez que para outras leguminosas, como exemplo, Stylosanthes guianensis, 9mg dm -3 em solução nutritiva, por doze dias de cultivo, causaram toxidez nas plantas (Amaral et al, 2000). Nolla et al (2007) observaram que o alumínio reduz consideravelmente o crescimento radicular das plântulas de leguminosas além de aumentar a espessura das raízes, inibindo a expansão das células da raiz, culminando no seu engrossamento.…”
Section: Resultsunclassified
“…Aluminium reduced NO3 uptake in soybean (8)(9) and in wheat (10) . On the other hand, Al increased absorption of nitrate in Stylosanthes guianensis and S. macrocephala (11)(12) .…”
Section: Introductionmentioning
confidence: 99%